Models and Morals: Elite-Oriented and Value-Neutral Discourse Dominates American Organizations' Framings of Climate Change. - Wetts, Rachel (Social Forces, 2020)
Is climate change discourse highly politicized and divisive, or has the debate instead become "post-political," oriented around consensus, problem-solving and administrative management? Adjudicating this debate is important for pragmatic and theoretical reasons. Pragmatically, these divergent characterizations suggest different barriers climate discourse might pose for engaging public concern and citizen mobilization. Theoretically, these characterizations provide different understandings of how elites respond to structural crisis. Using automated text analysis to describe a large corpus of organizations' press releases about climate change from 1985 to 2013 (N = 1,768), I find that this discourse has been largely expert-oriented and technocratic, neglecting concerns of values and identity widely believed to be important for social movement mobilization. Organizations predominantly frame climate change as a problem that, while real and serious, is best handled through the careful and deliberate work of scientific, political, and economic elites. Surprisingly, these observations remain true even among advocacy organizations. These findings provide empirical support that a "post-political" framing of climate change, where the issue is discussed in a way that neutralizes social and political power dynamics, dominates American organizations' official pronouncements about climate change. To the extent that earlier scholars are correct that conflict-oriented discursive strategies—such as identification of a common antagonist—are effective at rousing public concern, this discourse is unlikely to mobilize strong public emotion and activism.